Pakistan Labor Market Study : Regulation, Job Creation, and Skills Formation in the Manufacturing Sector - World Bank (Washington, DC, 2013)
In an effort to improve employment outcomes and industrial productivity, the Government of Pakistan (GoP) has launched a dual-track reform process involving broad-based overhaul of labor laws and institutions, and expansion and reform of the Vocational and Technical Training (VTT) system. Labor market regulation and laws are useful economic and social institutions designed to protect workers from undesirable consequences of market failure such as arbitrary or discriminatory actions by employers. They also help stabilize employment and household incomes against aggregate business cycles and shocks. Labor regulation is also an important element of society's instruments for the provision of social security and the maintenance of health, safety, and environmental standards in economic activities. Labor regulation in Pakistan is excessive by international standards, as can be seen from data on a number of indicators of labor market flexibility. All things considered, Pakistani industry and workers will seem to be better off with a more flexible labor market. The report analyzes the existing labor laws and institutions, along with the new draft laws, from this point of view. It also provides a review of the current VTT system and changes for it.